The Relationship Between Teacher’s Profession and Teachers' Teaching Ability on (Field Experience Program) PPL's Students of State University of Medan (Unimed) College Year 2005/2006 - Nur’aini Nur’aini (Budapest International Research and Critics University, 2018)
This study aims to look at the relationship between perception of the teacher profession and prospective teacher’ teaching ability on (Field Experience Program) PPL’s Students of State University of Medan. Teacher's profession according to community's perspective is still considered not too important. The community / parents of students sometimes ridicule and accuse the teacher of being incompetent, not qualified and so on. When their son / daughter cannot solve the problem that they face or they have no ability they want. The sample in this study are Unimed’s Student in 7th Semester as many as 96 people who have taken the Field Experience Program (PPL) using purposive sampling. The method of collecting data in this study are documentation and questionnaires. The documentation method is used to find out data about teaching abilities, GPA values, and macro values. While the questionnaire method of perception of the teaching profession is based on several indicators which are the core of the teacher's code of ethics as professional staff. The findings shows that there is a very significance positive of the relationship between perception of the teacher profession and prospective teacher’ teaching ability on (Field Experience Program) PPL’s Students and the index of student cumulative achievement with the ability of Unimed’s student, Freg = 19,845 with p <0,000. This means that the more positive the perception of the teaching profession and the higher the student's GPA, the better the ability to teach